1993
DOI: 10.1073/pnas.90.15.7401
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin A1 is required for stem elongation in spinach.

Abstract: The effects of the growth retardants 2'-isopropyl-4'-(trimethylammonium chloride)-5'-methylphenyl piperidine-l-carboxylate (AMO-1618) and calcium 3,5-dioxo-4-propionylcyclohexanecarboxylate (BX-112) on stem elongation were investigated in the rosette plant spinach (Spinacia oleracea L.) under long-day (LD) conditions. Stem growth induced by a LD treatment was prevented by both retardants. The inhibition caused by AMO-1618 was reversed by gibberelmin A1 (GA,) and GA20, whereas the effects of BX-112 were reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 17 publications
3
40
0
Order By: Relevance
“…The procedures for extraction, purification, and quantification of endogenous GAs have been described elsewhere (Talon et al, 1990;Zeevaart et al, 1993;Schomburg et al, 2003).…”
Section: Analysis Of Endogenous Ga Levelsmentioning
confidence: 99%
“…The procedures for extraction, purification, and quantification of endogenous GAs have been described elsewhere (Talon et al, 1990;Zeevaart et al, 1993;Schomburg et al, 2003).…”
Section: Analysis Of Endogenous Ga Levelsmentioning
confidence: 99%
“…Gibberellins activate cell division and cell enlargement processes in vegetative organs (Talon et al, 1991) and therefore are generally associated with the initiation of growth (Talon and Zeevaart, 1992). The endogenous GAs found in citrus fruits are mainly members of the 13-hydroxylation pathway [GA 53 , GA 97 , GA 44 , GA 17 , GA 19 , GA 20 , GA 29 , GA 1 , epi-GA 1 , and GA 8 (Goto et al, 1989;Turnbull, 1989;Talon et al, 1990a] leading to GA 1 , the bioactive GA (Zeevaart et al, 1993). This pathway also operates in vegetative tissues of citrus (Vidal et al, 2001(Vidal et al, , 2003 where is thought to control shoot growth and elongation (Fagoaga et al, 2007).…”
Section: Hormonal Regulators Of Fruit Growth and Abscissionmentioning
confidence: 99%
“…This is also true of spinach (Metzger and Zeevaart 1982), in which the conversion of GA 53 to GA 44 and of GA 19 to GA 20 are both regulated by daylength (Talon et al 1991). In addition, an earlier step in biosynthesis of ent-kaurene is also regulated by daylength (Zeevaart et al 1993). Wu et al (1996) subsequently showed that the level of GA 20 -oxidase mRNA is higher in plants in LD.…”
Section: Stem Elongation and Floweringmentioning
confidence: 83%